2009
DOI: 10.3177/jnsv.55.326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soybean Isoflavone on the Notch Signal Pathway of the Brain in Rats with Cerebral Ischemia

Abstract: SummaryThe aim of this study was to test the hypothesis that gastric lavage with soybean isoflavone activates the Notch signaling pathway and prevents apoptosis in the cerebral cortex during experimental strokes. Sprague-Dawley rats were randomly assigned to four groups of 10 rats each: sham operation plus vehicle (Sham), middle cerebral artery occlusion plus vehicle (MCAO), MCAO plus low dose soybean isoflavone (10 mg/(kg·d)) and MCAO plus high dose soybean isoflavone (50 mg/(kg·d)). The vehicle (saline, 10 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The literature revealed that results of gene expression analysis in experimental stroke are sometimes difficult to construe. Some reports completely lack information about the origin of the investigated tissue (Liu et al, 2009;Zhang et al, 2009); in other cases the entire cortices were used for analysis (Hoda et al, 2009;Huang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The literature revealed that results of gene expression analysis in experimental stroke are sometimes difficult to construe. Some reports completely lack information about the origin of the investigated tissue (Liu et al, 2009;Zhang et al, 2009); in other cases the entire cortices were used for analysis (Hoda et al, 2009;Huang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There have been many investigations for an application of flavonoids as anti-carcinogenic and radiosensitizing agents, because flavonoids display anti-inflammatory, anti-oxidant, anti-proliferative, and anti-bacterial activities (33,34). Some of the flavonoids, such as genistein, quercetin, baicalin, baicalein, and niclosamide, have been reported to regulate the Notch-1 pathway in various cancer cell lines (35)(36)(37)(38). Thus, we performed flavonoid screening and selected rhamnetin and cirsiliol as Notch-1-regulating candidates, which have been poorly studied in cancer.…”
mentioning
confidence: 99%
“…can potentially induce Notch signaling to promote neurogenesis and reduce neuronal apoptosis [29,30]. Here we show that intraperitoneal injections of IA, immediately after ischemia-reperfusion and continuing for 14 d, result in increased levels of NICD protein and Notch1, PS1, and HES1 gene expression, suggesting that IA promotes Notch activation.…”
Section: Effect Of Ilexonin a On The Notch Signaling Pathway Followinmentioning
confidence: 76%